2019
DOI: 10.3389/fevo.2019.00110
|View full text |Cite
|
Sign up to set email alerts
|

Prioritising Support for Cost Effective Rare Breed Conservation Using Multi-Criteria Decision Analysis

Abstract: Farm Animal Genetic Resources (FAnGR) are threatened by breed homogenisation. Rare breeds may carry important genes that allow breeders to respond to global production challenges including climate change and emerging disease risk. Yet, exploration of approaches to improve cost-effectiveness of investments in farm animal genetic diversity has been limited. We employ multi-criteria decision analysis (MCDA) to investigate how rare breed incentive schemes can be rationalised. A performance matrix was used to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The new algorithm, providing more reliable assessment of the risk status will help to prioritize support for conservation. As suggested by Wainwright et al, (2019)…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The new algorithm, providing more reliable assessment of the risk status will help to prioritize support for conservation. As suggested by Wainwright et al, (2019)…”
Section: Resultsmentioning
confidence: 83%
“…50<Nₑ≤ 200population in need of conservation; 200<Nₑ≤1000population in need of monitoring, Nₑ>1000population at no risk. Other criteria proposed in a number of studies include: the demographic trend (stable, downward, upward), inbreeding increment over a specific time frame, percentage of purebred males and females, information about the implementation (or lack) of conservation programmes, projected population growth in a given period of time, breed concentration in a country, number of herds and trends in population growth, and the degree of introgression (crossbreeding) per generation (Alderson, 2003(Alderson, , 2010FAO, 2004FAO, , 2013Verrier et al 2015;Wainwright et al, 2019).…”
mentioning
confidence: 99%
“…The annual evolution of BN and BC N es values when considering their reference populations (Figure 10), have shown a very irregular trend. Wainwright et al [80] suggested the use of N es and their contribution over 5 years to analyze the evolution of conservation activities.…”
Section: Inbreeding Analysis and Non-random Mating Ratementioning
confidence: 99%
“…The committee must use the information updated in the platform to monitor the breed's situation every year [23,24] by using conventional methods [25] or modern methodologies based on the multi-criteria analysis [26,27]. The committee must issue an annual national general report about the situation of national animal genetic resources, presented to the national commission and compiled together with those from microorganisms and plant committees to publish a joint annual national report on agrobiodiversity.…”
mentioning
confidence: 99%
“…In this respect, the first decision to be taken is the species, considering the level of endangerment that it faces, availability of specialized methods, technological and human resources, and the present and future value of the species for the country. The second decision to take is the breed to choose within the species, considering the prioritization methods previously mentioned to determine the breed contribution to the general biodiversity of the species [56,57], the genetic situation and value of the breed [58,59], its cultural value [60], or conjoined multicriteria methods [26,27]. The third decision to take is the selection of the recommended individuals within the breed.…”
mentioning
confidence: 99%